Improving Communication Competency Skills in Autism Spectrum Disorders in Adaptive Physical Learning Through Augmentative and Alternative Communication (AAC) - Lalan Erlani; Kawai Yasuhi; Muhammad Nurrohman Jauhari; Toni Yudha Pratama (Universitas Sultan Ageng Tirtayasa, 2026)
This study aims to improve the communication competence of children with Autism Spectrum Disorder (ASD) through the implementation of an Augmentative and Alternative Communication (AAC) system within Adapted Physical Education (APE) learning. The AAC system developed in this study comprises structured guidelines, instructional approaches, practical tutorials, strategies, and visually based learning methods specifically designed to support children with autism in educational settings. A mixed-methods research design was employed to comprehensively examine the effectiveness of the intervention. This approach integrates both qualitative and quantitative data collection and analysis to provide a more robust understanding of the research problem. The underlying assumption of this design is that combining qualitative and quantitative evidence yields deeper and more nuanced insights than relying on a single methodological approach. The findings demonstrate that AAC interventions effectively facilitate the development of communication functions among children with ASD. Consistent with prior research, the results indicate that AAC enhances speech production, functional communication, expressive language abilities, and receptive language skills. These outcomes suggest that integrating AAC into Adapted Physical Education can serve as an effective pedagogical strategy to promote communicative competence and social participation for children with ASD.